Tracking Water Quality from Source to Home: A showed Case of El Gorashi Locality, Gezira State, Sudan - Hassan, El Sidieg M. A.; Abdelgalil, Eltigani E. B. (Gezira Journal of Engineering and Applied Sciences; Vol 15 No 2 (2020), 2022)
Water quality is recognized one of the greatest challenges to human life because water may become unsafe at any point between collection and consumption.  This study was conducted in Elgorashi locality, Gezira State Sudan to investigate water sources physically and biologically. A number of 70 water samples were taken from various sources which include; irrigation canals, Haffir, Haffir Exit Basin (HEB), Slow Sand Filters (SSF), Clean Water Basin (CLB), homes taps and homes storage containers. The samples were collected from Elgorashi city, Galoka, Geneda, Maatoug and Hillat Babiker villages.  The results were compared to WHO risk category. Statistical results revealed that physically, 86% of water sources were suitable for human consumption. Biological analysis showed 73% of water sources were polluted with bacteria. It has been found that (19/70) 27.14% of all water sources were safe, (28/70) 40% at low-risk, (14/70) 20% at intermediate risk and (9/70) 12.86% were at high risk. A long the water supply network, the main water sources of irrigation canals and Haffirs were unsafe. At home level, 70% of taps water were classified under low risk category and 55% of storage containers showed high risk sources. These results indicate leakage at the water distribution network. The study recommends immediate disinfection intervention at all sources to protect community from illness associated with poor water quality. جودة الماء تعتبر من اهم التحديات لصحة الانسان  لان الماء قد يتعرض للتلوث في اي موقع  بين المصدر والمستهلك.  في هذا البحث تم اختبار نوعية الماء الطبيعية والبيولوجية في مدينة القرشي – ولاية الجزيرة في السودان.  تم  جمع 70 عينة ماء من مصادر  مختلفة شملت  قنوات الري والحفائر واحواض تجميع ماء الحفير واحواض تنقية الماء وحنفيات المنازل وادوات حفظ الماء المنزلية. تم جمع العينات من مدينة القرشي وابوقوتة وقرية جنيدا ومعتوق وحلة بابكر. تمت مقارنة النتائج مع مقاييس منظمة الصحة العالمية. اظهرت  نتائج التحليل الطبيعى ان 86% من المصادر تحتوي على ماء صالح لاستخدام الانسان. التحليل البكتيرى للماء اظهر ان 73% من المصادر ملوثة بالبكتريا. وجد ان نسبة 27.14% من  جملة المصادر تحتوي على ماء نظيف و 40% من المصادر تحتوي على ماء ذو خطورة منخفضة و 20% من المصادر تحتوى على ماء ذو خطورة متوسطة و12.86% من المصادر مياهها عالية الخطورة. على طول شبكة توزيع الماء تعتبر قنوات الري والحفائر مصادر ذات  ماء غير امن. 70% من حنفيات المنازل تحتوي على ماء ذو خطورة منخفضة و 55% من اواني حقظ الماء المنزلية تعتبر مياهها عالية الخطورة. دلت النتائج على وجود كسورات في خطوط توزيع الماء واوصت الدراسة على تطهير كل المصادر لحماية المجتمع من الامراض المرتبطة بالماء.